Development of portable data security module in tele-health system - Xu, Dan Dan (2015)
With the development of science and technology, people’s life is getting better and better in recent decades. In last few years, technology such as mobile health, tele-health applications are emerging fast. People can check their health status conveniently by using these technologies. However, confidentiality of the medical data becomes one of the main concerns due to its sensitive nature. The objective of this project was to develop encryption and decryption modules for security in tele-health applications. This project focused on the design and development of security modules for sensor-based networks. Software-based encryption and decryption modules were developed and integrated into existing programs for security improvement. The performance of the security modules was tested through observing the correctness of data encryption and decryption. The project covered different stages of design and development of security modules. Several factors were taken into account during implementations. For example, unstable communication channels, data loss, and key generations and so on. Further works such as key management and key distributions can be done to improve security levels in tele-health applications.